Association between vitamin D and calcium intakes, breast microcalcifications, breast tissue age-related lobular involution and breast density. Issue 12 (10th December 2022) - Clemenceau, Alisson; Chang, Sue-Ling; Hanna, Mirette; Durocher, Francine; Diorio, Caroline
Abstract : The results of this study suggest that the association between vitamin D and calcium intakes and breast cancer risk factors could be influenced by the presence of microcalcifications. Abstract: Objective: To demystify the potential role of vitamin D and calcium intakes in breast carcinogenesis, we explored the association between these two nutrients and three biomarkers of breast cancer risk: the presence of microcalcifications, age-related lobular involution and breast density. Methods: A total of 82 premenopausal and 79 postmenopausal women diagnosed with breast cancer completed a food frequency questionnaire to assess their total vitamin D and calcium intakes. Presence of microcalcifications was determined by reviewing pathology reports. Age-related lobular involution was assessed in nontumoral breast tissue on hematoxylin–eosin-stained slides and percent breast density was assessed by a computer-assisted method. Multivariate generalized linear models were used to evaluate associations between quartiles of vitamin D and calcium intakes and the biomarkers of breast cancer risk. Results: Increasing quartiles of vitamin D intake were inversely associated with the presence of microcalcifications (fourth quartile [Q4] prevalence ratio [PR] = 0.55; P trend = 0.021) and breast density (Q4-Q1 = −7.7%; P trend = 0.023) in postmenopausal women, and positively associated with age-related lobular involution in women with microcalcifications (Q4 PR = 1.62; P trend = 0.036). Increasing quartiles of calcium intake were inversely associated with microcalcifications among all (Q4 PR = 0.44), premenopausal (Q4 PR = 0.37) and postmenopausal women (Q4 PR = 0.38; P trend < 0.014 for all). It was also inversely associated with breast density in women without microcalcification (Q4-Q1 = −8.3%; P trend = 0.047), but positively associated with breast density in women with microcalcifications (Q4-Q1 = 10.0%; P trend = 0.032). Conclusions: Results suggest that the association between vitamin D and calcium intakes and breast cancer risk factors could be influenced by the presence of microcalcifications.